Ideals, realities and paradoxes of stakeholder participation in EU fisheries governance. Issue 2 (2nd April 2016) - Linke, Sebastian; Jentoft, Svein
Abstract : A participatory turn towards more democratic policy-making and decision-making that involves stakeholders has occurred in EU environmental governance since roughly 2000. Despite ubiquitous emphases in favour of 'good governance principles', we still know little about their effects in concrete settings where stakeholders are involved in policy and management. Two recent reforms of the EU's Common Fisheries Policy introduced stakeholder participation via so-called Advisory Councils (ACs). This involved establishing a system for stakeholder representation in these organisations. This paper shows how democratic ideals that emphasise including stakeholders in environmental governance such as fisheries become constrained – or even reversed – by the realities of stakeholder representation procedures. Our theoretical discussion refers to tensions between democratic ideals and the effective organisation of stakeholder participation through representation, emphasising constraints on participation and what may be lost or gained through the selection processes that representation involves. Our empirical study of the Baltic Sea AC shows how unresolved problems regarding representation create legitimacy issues, which are associated with the AC system in general and which we argue ultimately reduce such organisations' opportunities to contribute to a more progressive and sustainable environmental governance.